2022
DOI: 10.1007/s12035-022-02856-w
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Peroxisome Proliferator-Activated Receptor-gamma in 3-Nitropropionic Acid-Induced Striatal Neurotoxicity in Rats

Abstract: Telmisartan (TEL) is an angiotensin II type 1 receptor blocker and a partial activator of peroxisome proliferator-activated receptor-gamma (PPARγ), which regulates inflammatory and apoptotic pathways. Increasing evidence has demonstrated the PPARγ agonistic property of TEL in several brain disorders. This study aims to explore the neuroprotective impact of TEL in 3-nitropropionic acid (3-NP)-induced neurotoxicity in rats. The PPARγ effect of TEL was affirmed by using the PPARγ agonist pioglitazone (PIO), and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 108 publications
0
8
0
Order By: Relevance
“…Recent studies have identified a significant role for pathways of programmed cell death that can ultimately control cell survival and cognitive impairment during MS [46,61,128,130,132,134,[200][201][202] (Table 1). Programmed cell death pathways that involve autophagy, apoptosis, pyroptosis, and ferroptosis can influence cell survival during inflammation [34,39,66,73,74,85,87,[203][204][205][206][207][208][209][210][211][212][213], oxidative stress [10,45,77,86,89,93,119,185,[214][215][216][217][218][219], ischemia [219][220][221][222][223], and mitochondrial dysfunction [32,…”
Section: Autophagy Apoptosis Pyroptosis and Ferroptosis Involvement I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have identified a significant role for pathways of programmed cell death that can ultimately control cell survival and cognitive impairment during MS [46,61,128,130,132,134,[200][201][202] (Table 1). Programmed cell death pathways that involve autophagy, apoptosis, pyroptosis, and ferroptosis can influence cell survival during inflammation [34,39,66,73,74,85,87,[203][204][205][206][207][208][209][210][211][212][213], oxidative stress [10,45,77,86,89,93,119,185,[214][215][216][217][218][219], ischemia [219][220][221][222][223], and mitochondrial dysfunction [32,…”
Section: Autophagy Apoptosis Pyroptosis and Ferroptosis Involvement I...mentioning
confidence: 99%
“…However, the loss of membrane PS asymmetry is reversible, and if membrane asymmetry is restored, injured cells are then given the ability to recover, and not be engulfed by inflammatory cells [197,[270][271][272]. With the later phase that involves deoxyribonucleic acid (DNA) degradation in the cell [34,40,77,226,[273][274][275], caspase activation plays a prominent role [15,77,194,206,210,273,[276][277][278]. This process of caspase activation and DNA destruction is irreversible [259].…”
Section: Autophagy Apoptosis Pyroptosis and Ferroptosis Involvement I...mentioning
confidence: 99%
“…If the second phase of apoptotic cell death is reached, it is usually not reversible and involves the degradation of nuclear deoxyribonucleic acid (DNA) [136,137,167,169,[290][291][292][293][294]. The second stage of apoptosis consists of mitochondrial membrane depolarization, cytochrome c release, and caspase activation [136,193,252,290,[295][296][297][298][299][300]. Apoptosis during DM can lead to atherosclerotic plaque generation [296,301,302], foster processes associated with infection, such as COVID-19 [59,71,303,304], promote joint degenerative diseases [152,293,[305][306][307], and enhance stem cell demise and inflammatory pathway activation [26,103,129,132,291,[308][309][310][311][312][313][314].…”
Section: Cellular Mechanisms Of Oxidative Stress Energy Metabolism An...mentioning
confidence: 99%
“…Apoptosis during metabolic disorders also can be involved in adipose tissue inflammation during loss of metabolic homeostasis [315], may lead to cognitive loss in combination with autophagic pathways [77], promote microglial activation to the detriment of cells [26], impair pancreatic β-cell function [61,316], promote demyelination of nerve fibers [317], lead to ischemic cell injury [63], result in retinal cell loss [75,76,292,[318][319][320][321], foster renal cell injury [43,220,322], and lead to vascular cell degeneration [53, 101,215,277,323]. In particular, microglia are important for removing damaged cells during membrane PS externalization and apoptosis [106,131,145,277,278,298,308,[324][325][326][327]]. Yet, microglia can lead to the generation of oxidative stress through the production of ROS [8,165,167,246,250,[328][329][330][331], which can require modulation by non-coding RNAs [251,[332]…”
Section: Cellular Mechanisms Of Oxidative Stress Energy Metabolism An...mentioning
confidence: 99%
“…Based on the fact that neuronal PPARγ knockout in the prefrontal cortex of mice induces depressive-like behavior, PPARγ agonist, rosiglitazone, has an antidepressant-like effect on stressed mice [12][13][14]. The activation of PPARγ inhibits in ammatory response via increasing anti-in ammatory cytokines expression or suppressing pro-in ammatory molecules, which contributes to injured brain repairment [15,16]. However, the role of microglial PPARγ in emotional behavior is still unclear.…”
Section: Introductionmentioning
confidence: 99%